The Maidan massacre in Ukraine: the mass killing that changed the world - Katchanovski, Ivan (Rethinking political violence, 2024)
This book provides a comprehensive analysis of the Maidan massacre in Ukraine. It uses a theoretical framework of rational choice, moral hazard, state- repression backfire, and Weberian ideas about rational action to explore the massacre.